A systems model of using the Deliberate Leadership® framework for addressing wicked problems. (2018) - Peterson, Gayle; Yawson, Robert M.; Sherman, John; Johnson-Kanda, Ivy
This study is predicated on the premise that addressing wicked problems through business practices and social innovations will need new leadership and organisational development strategies for helping organisations mirror practices and approaches internally with staff and externally with stakeholders. The Deliberate Leadership® Model was developed as a subsequent of this need. This study illustrated the key implications for practice and for research of the Deliberate Leadership model using a multi-case study approach. The paper reviews wicked problems and discusses the epistemological genesis of the Deliberate Leadership framework. Using a multi-case method approach, the Deliberate Leadership is illustrated, and a baseline understanding of the use of the Deliberate Leadership approach in addressing wicked problems is discussed. A systemic model depicting the critical links in identifying wicked problems and the use of the Deliberate Leadership Framework (DLF) for addressing 'wickedly' complex problems is developed.